EFL Learners’ Anxiety versus Learning Strategy and Literal Listening Score: How Do They Correlate? - Hidayanti, Ika; Azami, Mochammad Imron (Soegijapranata Catholic University, 2023)
This recent study is aimed at identifying the correlation between the EFL learners’ strategy attainment and the listening score controlled by anxiety in the literal listening class and to know the causes and selected strategies to reduce anxiety. Some instruments were utilized in this study including the questionnaires on anxiety and learning strategies, and their final score. A semi-structured interview was also used to elicit the EFL learners’ experiences in the class. Participated in the study, 40 second-semester students taking the literal listening class were required to fill out the two questionnaires and their target from the final listening score was also counted. This mixed-method research utilized descriptive and correlation statistics addressed to answer the research focuses, and analyze the interview transcripts descriptively. The first finding was that there were three different distributions of scores, with “Good” category learners who experienced high anxiety. Further, strategy deployment correlated moderately and significantly with the EFL learners’ proficiency in listening class. More specific results indicated that they felt anxious when the class activities were on test or quiz time and related to the task types of literal listening. To solve such anxiety, some of the students focused on using keywords, and some are guessing the context. Few of them matched the questions to the context and searched in Google for the meaning. It is expected that EFL teachers elicit and level problems of anxiety from the early stages to determine appropriate and effective strategies to cope with and lead to better proficiency.